2000
DOI: 10.1007/s005860000152
|View full text |Cite
|
Sign up to set email alerts
|

Pain pattern in multiple vertebral hemangiomas involving non-adjacent levels: report of two cases

Abstract: IntroductionHemangioma is a benign tumor consisting of blood vessels. There are two types: generalized and localized. In the generalized type there is involvement of multiple organs such as the liver, skin and bone [7]. Localized hemangiomas are the most common. In the skeleton, the most common site is the spine, followed by the skull and pelvis. Hemangiomas are often asymptomatic and discovered accidentally, but they may cause back pain or spinal cord compression in some cases. Radiographic and CT evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Multiple vertebral hemangiomas may present with different clinical characteristics over a long period. 10 Plain film radiographic findings of hemangioma are characteristic. Typical radiographic findings include coarse axial contrast-enhanced T1-weighted image (B) reveal continued complete replacement of the marrow at the L1 lumbar vertebra and a moderate-sized persistent epidural mass, only slightly diminished compared with the earlier examination.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple vertebral hemangiomas may present with different clinical characteristics over a long period. 10 Plain film radiographic findings of hemangioma are characteristic. Typical radiographic findings include coarse axial contrast-enhanced T1-weighted image (B) reveal continued complete replacement of the marrow at the L1 lumbar vertebra and a moderate-sized persistent epidural mass, only slightly diminished compared with the earlier examination.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of symptomatic hemangioma is unknown. 5 Fox and Onofrio reported that 35 of 59 patients with vertebral hemangioma (59%) were asymptomatic; that 13 (22%) had only local pain, and that 11 (19%) exhibited abnormal neurologic findings. 9 Neurologic impairment from vertebral hemangioma results from a variety of mechanisms, including the following: compression fracture of the involved vertebra; sudden hemorrhage into the extradural space; subperiosteal growth of the tumor creating an extradural mass producing compression; spinal cord ischemia caused by steal phenomenon 11,12 ; hypertrophy of the posterior cortex of the vertebral body or enlargement of the lamina and facets as a result of the angiomatous invasion 6,[11][12][13][14][15][16] and compression from anomalous vessels draining or feeding the lesion.…”
Section: Discussionmentioning
confidence: 97%
“…Also methacrylate may leak into spinal canal and this may produce spinal cord or nerve damage and pulmonary embolism. 5,19 Percutaneous intralesional injection of ethanol or a sclerosing substance is used for decreasing size of hemangioma. 6 Critical to the effectiveness of this method is the requirement that the ethanol be injected into the vascular space of the hemangioma and not leak out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,18,23,24 Notably, intervertebral disc lesions are painful, 25 and pain supposedly related to VHs has been found to closely resemble symptoms of disc lesions. 26 It is thus possible that back pain in cases of VHs is due to the co-occurrence with disc lesions.…”
Section: Disc Lesionsmentioning
confidence: 95%